STORYTELLING IN TEACHING LITERACY IN AN EFL CLASSROOM : A Descriptive Study of Eighth Grade Students of a Private Junior High School in Cipatat, West Bandung - Satriani, Intan (2016)
This paper reports a study on the implementation of storytelling technique in teaching literacy to second graders of junior high school in West Bandung. The study aims to investigate the way of implementing storytelling in teaching literacy. It finds out the advantages and constrains in implementing storytelling in teaching literacy. The study employed a descriptive qualitative research design. The data were obtained from several instruments, namely class observations, students' interviews and students' writing products which were analyzed using writing assessment criteria. The findings revealed that the teaching program which was implemented in seven units was successful to develop students' literacy ability. Specifically, they showed improvement on reading comprehension and interest. Besides that, in writing they showed their development in schematic structures, grammar roles, and graphic features. Moreover, the data from observations, interviews, and documentation of students' texts showed some benefits and challenges in implementing the teaching program. These include (1) developing students' literacy ability; (2) arousing students' imagination; (3) enriching students' vocabulary; and (4) developing students' reading awareness and interest. Besides benefits, some challenges also found in this study. The challenges had something to do with students' proficiency and length of texts. Based on those findings, it is suggested that this teaching program will be more effective if it is applied in the regular teaching using classroom action research. ; Tesis ini melaporkan sebuah penelitian tentang penerapan teknik storytelling dalam pengajaran literasi untuk siswa kelas dua sekolah menengah pertama di Bandung Barat. Penelitian ini bertujuan untuk menginvestigasi tahapan pengimplementasian storytelling dalam pengajaran literasi dan keuntungan penggunaan teknik ini. Penelitian ini menggunakan desain penelitian kualitatif deskriptif. Data dalam penelitian ini diperoleh dari beberapa instrumen, yaitu observasi kelas, interview siswa dan hasil menulis siswa yang dianalisis menggunakan kriteria penilaian menulis. Hasil temuan penelitian ini menyatakan bahwa program pengajaran yang diterapkan dalam tujuh unit dapat mengembangkan kemampuan literasi siswa. Secara spesifik, beberapa siswa menunjukkan perkembangan dalam memahami teks bacaan dan ketertarikan dalam membaca. Selain itu, dalam menulis mereka menunjukan perkembangan terutama dalam penggunaan tata bahasa dan struktur penulisan. Selanjutnya, data dari observasi, interview, dan teks hasil kerja siswa menunjukkan beberapa kelebihan dan hambatan dalam pengimplementasian program pengajaran. Hal tersebut meliputi (1) mengembangkan kemampuan literasi siswa; (2) meningkatkan imaginasi siswa; (3) memperkaya perbendaharaan kata siswa; dan (4) mengembangkan kesadaran dan ketertarikan membaca siswa. Selain kelebihan diatas, beberapa hambatan juga ditemukan di penelitian ini. Hambatan tersebut berhubungan dengan kemampuan bahasa Inggris siswa dan panjang teks bacaan. Berdasarkan temuan tersebut, penelitian ini merekomendasikan bahwa program pengajaran ini dapat lebih efektif jika diaplikasikan saat pengajaran di kelas dengan menggunakan penelitian tindakan kelas.